A REVIEW OF THE HISTORICAL EVIDENCES OF CHILD BIRTH FROM VEDAS AND OTHER SCRIPTURES - Ramya Karanam; Dr.K.Ramesh Babu (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The ancient Indian cognitive constructs pertaining to children and adolescents exhibit a striking resemblance to their contemporary modern counterparts. The ancient ideologies were founded upon a profoundly optimistic perspective regarding the progression of children's growth, scholastic pursuits, and eventual self-sufficiency, as well as the pivotal role and societal impact of adults. The concept of procreation and the subsequent cherishing of offspring has long been held in high regard within societal norms. The youthful progeny was systematically classified into four distinct varnas, predicated upon their cognitive acumen, proficiencies, commendable qualities, and innate propensities. SubsequentSly, they were imparted education commensurate with their respective classifications, in the seclusion of Gurukuls, far removed from their familial abodes. They possessed an inherent entitlement to receive education on a global scale. Females were afforded commensurate levels of attention as their male counterparts. The male offspring were anticipated to procure their sustenance, whereas the female offspring were anticipated to assume the role of domestic caretakers. The culmination of the educational journey and the subsequent return to one's abode symbolized the liberation from the transitional phase of adolescence. The well-being of children's physical and mental health, as well as the associated disorders, has been duly acknowledged and addressed. The etiology and treatment of physical and mental disorders were aligned with the prevailing scientific advancements of the respective eras.